1993
DOI: 10.1016/s0022-5347(17)35432-0
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Abscess Following Intravesical Bacillus Calmette-Guerin for Bladder Cancer: A Case Report

Abstract: An 87-year-old man with an abdominal aortic aneurysm received intravesical bacillus Calmette-Guerin therapy for transitional cell carcinoma of the bladder. He presented 9 months later with a psoas abscess that mimicked a contained retroperitoneal abdominal aortic aneurysm rupture. The abscess cultures yielded Mycobacterium bovis. Recent transurethral resection and high voiding pressures after instillations of bacillus Calmette-Guerin may have led to distant dissemination of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 11 publications
0
14
0
3
Order By: Relevance
“…Vertebral osteomyelitis in these patients is thought to result from hematogenous dissemination of BCG infection. [1011151725] Although an immunity-mediated hypersensitivity reaction could theoretically underlie the granulomatous inflammatory response in the spine, identification of M. bovis in all cases (including our case) strongly suggests an actual dissemination of the bacillus from the bladder to the spine. Vascular dissemination and large-vessel mycotic vasculitis have been described following intravesical BCG immunotherapy, lending further support to hematogenous spread as a pathogenetic mechanism.…”
Section: Discussionmentioning
confidence: 74%
“…Vertebral osteomyelitis in these patients is thought to result from hematogenous dissemination of BCG infection. [1011151725] Although an immunity-mediated hypersensitivity reaction could theoretically underlie the granulomatous inflammatory response in the spine, identification of M. bovis in all cases (including our case) strongly suggests an actual dissemination of the bacillus from the bladder to the spine. Vascular dissemination and large-vessel mycotic vasculitis have been described following intravesical BCG immunotherapy, lending further support to hematogenous spread as a pathogenetic mechanism.…”
Section: Discussionmentioning
confidence: 74%
“…Seelig et al 26 reported a case series of 8 patients with BCG mycotic vascular infections of large arteries. Metastatic complications such as infection of implantable devices, 27 prosthetic joints, 28 and psoas abscesses 29,30 have also been described. Osteomyelitis after BCG vaccination is rare, with an incidence of 1 in a million, with most incidences occurring in long bones.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for complications from BCG instillation include traumatic catheterization, urethral injury during BCG instillation, bladder biopsy, hematuria, active infection, immunosuppression, bladder outlet obstruction, radiation cystitis, and transurethral resection of the prostate and deep bladder tumor within two weeks of instillation. [6][7][8][9][10][11] BCG organisms have been documented in the bladder up to 16.5 months after completion of BCG intravesical instillation therapy. 6 Long lasting and persistent BCG DNA in the bladder wall after intravesical BCG therapy may account for long-term immuneactivation and immune anticancer effects, and may explain why patients are still at risk of disseminated infection for months and even years after BCG therapy.…”
Section: Discussionmentioning
confidence: 99%